ANALISIS PENGARUH JUMLAH NASABAH, PENDAPATAN DAN HARGA EMAS TERHADAP TINGKAT PENYALURAN GADAI SYARIAH (RAHN) PADA PT PEGADAIAN (PERSERO) PER TAHUN 2012-2017 - Teni Rubiyanti (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
The study aims to analyze the influence of The Number of Sharia Pawn’s Customers, Business Revenue of Sharia Pawn, and Gold Prices to Sharia Pawn (Rahn) in PT Pegadaian. The data used in this study in the data montly from January 2012 – December 2017. The study is using the method of analysis of the regression linear risks by using a computer program EViews 9.0, and was be helped by microsoft Excel 2013.. The result showed a partial The Number of Sharia Pawn’s Customers signficantly influences on Sharia Pawn (Rahn) with the sig. 0.0000< 0.05. Business Revenuesof Sharia Pawn signficantly influences on Sharia Pawn (Rahn) with the sig. 0.0000 < 0.05. Gold Prices significantly influences on Sharia Pawn (Rahn) with the sig. 0.0302 > 0.05. The result showed that The Number of Sharia Pawn’s Customers, Business Revenues, and Gold Prices, simultaneously or together have a significant influence on the Sharia Pawn (Rahn) with the sig. 0.000 <0.05.